THE INFLUENCE OF APPARATUS COMPETENCE, QUALITY OF ACCOUNTING INFORMATION SYSTEM, AND WORKLOAD ON THE PERFORMANCE OF OFFICIALS MAKERS OF KARIMUN DISTRICT GOVERNMENT COMMITMENT WITH INTERNAL CONTROL SYSTEM AS MODERATING VARIABLE - Lumanto, Lumanto; Satriawan, Bambang; Irfan, Irfan; Khaddafi, Muammar (RADJA PUBLIKA, 2022)
This study aims to see the effect of Apparatus Competence, Quality of Accounting Information Systems, and Workload on the Performance of Commitment Making Officials of the Karimun Regency Government with the Internal Control System as a Moderating Variable. The type of research used is quantitative research. The sampling technique used is non-probability sampling with the saturated sample method (census). The population and sample in this study were allcommitment-making officials (PPK) in all Regional Apparatus Organizations of Karimun Regency, Riau Islands Province. The type of data used is primary data with data collection techniques using questionnaires. The analysis technique used is descriptive statistical analysis, data quality test, outer model test, inner model test, and hypothesis testing. In this study using SPSS version 26 for windows and SmartPLS. The results of this study indicate that: apparatus competence has a positive and insignificant effect on PPK performance with a T-statistical value of 1.418 < 1.96 and a P-value of 0.156 > 0.05, the quality of accounting information systems has a positive and significant effect on PPK performance with a T-statistic value of 3.307 > 1.96 and P-value 0.001 < 0.05,